Novel approach to the 3D printing of biphasic calcium phosphate/molybdenum disulfide composite reinforced with polyamide12 - Ananth K.P.; Jayram N.D.; Muthusamy K. (KeAi Communications Co., 2025)
In practical terms, the successful treatment of critical-sized bone defects remains a formidable obstacle. Among various options for bone regeneration, a customized 3D composite scaffold is widely acknowledged as the optimal choice. In the present study, we have developed a specialized composite scaffold utilizing biphasic calcium phosphate/molybdenum disulfide (BCp/MoS2) reinforced with polyamide12 (PA12) through the selective laser sintering (SLS) technique, employing different laser powers: 16W, 18W, 20W, and 22W. Notably, the BCp/MoS2/PA12 scaffold described in this research has not been explored in previous investigations. Analysis using a 3D profilometer reveals that the surface properties of the scaffold exhibit a robust mechanical interconnection between the 3-wt percent (Wt%) BCp/MoS2 composite within the PA12 matrix, particularly at a laser power of 22W. Remarkably, the mechanical properties of BCp/MoS2/PA12, including tensile strength (47.64 0.42 MPa) and Young's modulus (2.31 0.15 MPa), surpass those of pure PA12. These enhanced mechanical characteristics hold promising implications for the future advancement of bone tissue engineering. To comprehensively evaluate the composite scaffolds, we thoroughly investigated their thermal behavior and conducted morphological analysis. Moreover, after 21 days, in vitro live/dead results exhibited living cells along with their distinctive filopodia morphology, providing compelling evidence of the composite's non-toxicity. Further cell adhesion results showed enhanced growth, multiplication, and more reliable attachment and spreading across the composite surface. Encouragingly, the observed biological activity of the BCp/MoS2/PA12 scaffold with a 3 wt% concentration at a laser power of 22W suggests its significant potential for application in implant-related scenarios. ? 2023 The Authors